1998
DOI: 10.1136/jnnp.64.2.197
|View full text |Cite
|
Sign up to set email alerts
|

MRI lesion volume measurement in multiple sclerosis and its correlation with disability: a comparison of fast fluid attenuated inversion recovery (fFLAIR) and spin echo sequences

Abstract: Objectives-To assess whether multiple sclerosis lesion volume measurements derived using the fast fluid attenuated inversion recovery (fFLAIR) sequence show better reproducibility or correlation with disability than those derived using the conventional spin echo (CSE) sequence. Methods-Part I: twenty five patients with multiple sclerosis were scanned with CSE, fast spin echo (FSE), and fFLAIR. Lesion volume was determined twice for each sequence using a local threshold segmentation technique. Part II: fifty si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 32 publications
3
35
0
Order By: Relevance
“…This is consistent with the results of previous studies of untreated cohorts. 18,19 In the placebo-treated group, median TLV increased significantly year after year. The overall percentage increases from baseline (1.6%, 2.4%, and 10%, at 1, 2, and 3 years, respectively) are somewhat lower than those reported in previous relapsing-remitting placebo cohorts (ϳ5-10% per annum); this largely reflects the much higher baseline TLV in the secondary progressive cohort, and the absolute increase in TLV is similar to that found in early relapsing-remitting cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results of previous studies of untreated cohorts. 18,19 In the placebo-treated group, median TLV increased significantly year after year. The overall percentage increases from baseline (1.6%, 2.4%, and 10%, at 1, 2, and 3 years, respectively) are somewhat lower than those reported in previous relapsing-remitting placebo cohorts (ϳ5-10% per annum); this largely reflects the much higher baseline TLV in the secondary progressive cohort, and the absolute increase in TLV is similar to that found in early relapsing-remitting cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the sensitivity of MRI in detecting active MS lesions and, as a consequence, the statistical power of such trials [25,30], the value of several unenhanced MRI techniques has been recently assessed [2,4,8,10,11,29,31]. Dual-echo fast spin echo imaging (FSE) [4,29,31] can detect as many new MS lesions as conventional spin echo imaging (CSE), with significantly shorter scanning times, whereas the use of monthly fast fluid-attenuated inversion recovery (FLAIR) scans [10,11,31] can detect about 10% more new lesions than CSE [8].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study comparing fast FLAIR and T2-weighted images showed similar, modest correlations between lesion load and EDSS (Gawne-Cain et al 1998), with somewhat better correlations in RR than progressive forms of MS. Overall, current evidence in established MS indicates that the total extent of brain lesions correlates only modestly with locomotor disability.…”
Section: (I) Clinical Scalesmentioning
confidence: 94%